c-Fos rhythm in subdivisions of the rat suprachiasmatic nucleus under artificial and natural photoperiods - Jác, M; Sumová, A; Illnerová, H (American journal of physiology. Regulatory, integrative and comparative physiology, 2000)
Recent studies have shown that the waveform of the rhythm of c-Fos photoinduction in the ventrolateral (vl) part of the suprachiasmatic nucleus (SCN) and that of the rhythm in the spontaneous c-Fos production in the dorsomedial (dm) part of the SCN in rats released into constant darkness depend on the photoperiod under which the animals were previously maintained. The aim of the present study was to find out how the rhythms of c-Fos immunoreactivity in both SCN subdivisions are affected by actual light-dark (LD) cycles with various photoperiods, either artificial or natural ones, that animals may usually experience. Rats were maintained under artificial LD cycles, with either a long (16-h photoperiod) or a short (8-h photoperiod) or under natural daylight. In the latter case, c-Fos rhythms were followed in the summer when the photoperiod lasted about 16 h or in winter when it lasted only 8 h. The rhythms of c-Fos immunoreactivity under natural daylight did not differ significantly from those under corresponding artificial photoperiods. Under a long photoperiod, the morning c-Fos rise in the dm- as well as in the vl-SCN occurred about 4 h earlier than under a short one. In both SCN subdivisions, the interval when the nighttime c-Fos immunoreactivity was low, was shorter under a long than under a short photoperiod by roughly 6 h. The morning c-Fos rise in the dm-SCN always preceded that in the vl-SCN. Whereas in the former one the rise was due to the endogenous dm-SCN rhythmicity, in the latter one the rise was induced by the morning light onset. The results show that whereas c-Fos rhythmicity under actual LD cycles is affected by the photoperiod in both SCN subdivisions, mechanism of c-Fos induction in the dm-SCN differs from that in the vl-SCN.
Keywords: fotoperioda; Male; Rats, Wistar; geny fos; Genes, fos; osvětlení; Photoperiod; tma; imunohistochemie; mužské pohlaví; Suprachiasmatic Nucleus; potkani Wistar; neurony; cirkadiánní rytmus; světlo; Circadian Rhythm; krysa rodu Rattus; Animals; Immunohistochemistry; roční období; nucleus suprachiasmaticus; Seasons; zvířata; Neurons; Lighting; Rats; Darkness; protoonkogenní proteiny c-fos; Light; Proto-Oncogene Proteins c-fos